Mekanisme dan Prosedur Penyelesaiaan Kredit Macet yang diikat dengan Hak Tanggungan yang Dijual Secara Sukarela Pada PT BRI Sidempuan - Khoirunnisa, Nabila; Kamello, Tan; Harianto, Dedi; Andrianti , Syarifah Lisa (Program Studi Hukum Universitas Nusa Putra, 2024)
A loan secured by a mortgage, if the debtor defaults or breaches the agreement, meaning the debtor is unable to fully repay the debt to the bank, and it ultimately becomes a non-performing loan, requires the bank, as the creditor, to take prompt action to resolve the issue. The fastest solution for the bank to settle the non-performing loan is to conduct the sale of the mortgaged property at the local State Property and Auction Service Office (KPKNL). The objective of this study is to understand the mechanism for resolving non-performing loans secured by a mortgage through voluntary sale at the BRI Padangsidimpuan Branch. The method used in this study is normative legal research, which refers to legal norms and is conducted through literature review to obtain secondary data in the form of primary, secondary, and tertiary legal materials related to the issues being studied. This research is descriptive-analytic in nature. The study is based on relevant regulations and legal materials, with field research conducted at the BRI Padangsidimpuan Branch. The data analysis method used is qualitative, obtained through interviews with representatives of the BRI Padangsidimpuan Branch. The research findings reveal that the legal provisions for resolving non-performing loans secured by a mortgage that are sold voluntarily relate to the execution of the mortgaged property. The mechanism and procedure for resolving non-performing loans secured by a mortgage and sold voluntarily at the BRI Padangsidimpuan Branch involves two strategies: loan recovery and loan settlement